Pengaruh Penerapan Model SQ4R Terhadap Keterampilan Membaca Pemahaman Siswa Kelas IV Sekolah Dasar - Ramadhani, Axelia; Halidjah, Siti (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study's purpose is to analyze how the SQ4R learning model has affected the reading comprehension abilities of fourth graders at SD Muhammadiyah 2 Pontianak. A quasi-experimental design with an unequal control group is the sort of research methodology that was employed. All 127 pupils in Grade IV Regular at SD Muhammadiyah 2 Pontianak made up the study's sample. Because the sample utilized was a representative sample of the population, the sampling approach employed was a nonprobability sampling technique with purposeful sampling. The method of gathering the data is a measurement method. Multiple choice questions served as the research tool. The average post-test value for the experimental class was 81.75 on average, compared to 76.37 for the control class, according to the analysis of the data. Ha is accepted based on the t test calculation findings, which came out with a 2.036. The outcome is 0.5873 in the medium criterion according to the findings of the impact size calculation. The adoption of the SQ4R learning model (survey, question, read, reflect, recite, review) has a favorable impact on the reading comprehension abilities of fourth grade pupils at SD Muhammadiyah 2 Pontianak, it may be determined.